Social Media Marketing Mediated Changes In Consumer Behavior From E-Commerce To Social Commerce - Yoesoep Edhie Rachmad (International Journal of Economics and Management Research, 2022)
Social commerce is growing rapidly in Indonesia due to the ease of use of social media applications. There is a phenomenon in online commerce known as social commerce, where e-commerce users make purchases through social media. Online shopping capabilities on social media have led some e-commerce users to turn to social media for shopping. The aim of this research is to examine and analyze the influence of social commerce on customer switching behavior of e-commerce customers of Tokopedia, Lazada, Shopee, Blibli.com, and Bukalapak, as well as the role of social media marketing mediation on social media Facebook, Instagram, and Tiktok in social influence commerce on customer switching behavior. This research uses a quantitative method, using 300 respondents. The study is located in Jakarta, Bandung, Surabaya, Yogyakarta and Semarang. The results of this research are (1) Social commerce has a positive and significant impact on customer conversion behavior and social media marketing. (2) Social media marketing has a significant positive impact on customer switching behavior, and mediates the impact of social commerce on customer switching behavior. (3) Social Media Marketing has changed the behavior of consumers who not only buy products, but also participate in marketing by liking, sharing and commenting on the product content. Social Media Marketing also changes the behavior of sellers who not only sell products, but also create viral content for their products. (4) The government needs to evaluate, supervise and separate social media and social commerce to protect consumers, business actors and the e-commerce industry.